2021
DOI: 10.1186/s12974-020-02056-0
|View full text |Cite
|
Sign up to set email alerts
|

P2X7R-mediated autophagic impairment contributes to central sensitization in a chronic migraine model with recurrent nitroglycerin stimulation in mice

Abstract: Background Central sensitization is an important pathophysiological mechanism of chronic migraine (CM). According to our previous studies, microglial activation and subsequent inflammation in the trigeminal nucleus caudalis (TNC) contribute to the central sensitization. The P2X7 receptor (P2X7R) is a purinergic receptor expressed in microglia and participates in central sensitization in chronic pain, but its role in CM is unclear. Numerous studies have shown that P2X7R regulates the level of au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 74 publications
0
42
0
Order By: Relevance
“…In conditions of trauma such as spinal cord injury that are accompanied by elevated ATP and autophagic dysregulation (Galluzzi et al, 2016;Li et al, 2019), the modulation of microglial activation state has been proposed to enhance repair (Hu et al, 2015;Akhmetzyanova et al, 2019;Kobashi et al, 2020). However, treatment timing is critical, as transient P2X 7 receptor stimulation may enhance autophagy and promote M2a microglia, while sustained stimulation can inhibit autophagy and promote proinflammatory M1 microglia (Fabbrizio et al, 2017;Jiang et al, 2021). The P2X 7 receptor plays a complex role in microglial cells in balancing clearance with inflammatory signals; deeper mechanistic investigations may reveal more specific therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In conditions of trauma such as spinal cord injury that are accompanied by elevated ATP and autophagic dysregulation (Galluzzi et al, 2016;Li et al, 2019), the modulation of microglial activation state has been proposed to enhance repair (Hu et al, 2015;Akhmetzyanova et al, 2019;Kobashi et al, 2020). However, treatment timing is critical, as transient P2X 7 receptor stimulation may enhance autophagy and promote M2a microglia, while sustained stimulation can inhibit autophagy and promote proinflammatory M1 microglia (Fabbrizio et al, 2017;Jiang et al, 2021). The P2X 7 receptor plays a complex role in microglial cells in balancing clearance with inflammatory signals; deeper mechanistic investigations may reveal more specific therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…These mediators then bind to specific receptors of neurons and promote central sensitization, resulting in spontaneous pain, hyperalgesia and abnormal pain [ 10 ]. Our previous research also showed that activated microglia promote central sensitization by releasing proinflammatory factors and neurotrophic factors in the TNC of CM [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Koumine inhibits astrocyte activation and proin ammatory cytokines releasing by promoting autophagy, thus alleviating neuropathic pain [35]. Also, P2X7R antagonist Brilliant Blue G promotes autophagy to alleviate microglia activation of trigeminal nucleus caudalis and relives chronic migraine [36]. We showed for the rst time that autophagy was reduced in in amed skin tissues, which was promoted by EA.…”
Section: Discussionmentioning
confidence: 76%